Issues in the rehabilitation of failed residential projects in Malaysia: Clash between the interests of purchasers and secured creditor chargee - Md Dahlan, Nuarrual Hilal (Inderscience Enterprises Ltd., 2014)
One of the main problems in the Malaysian housing industry is the failed residential projects.It is evident that Malaysian laws are inadequate to protect the interests of the stakeholders, especially the purchasers, in failed residential projects.This paper analyses the liquidation law and issues in one of the failed residential projects in Malaysia, particularly the position of the secured creditor chargee and the purchasers. This paper finds that the secured creditor chargee of the liquidated housing developer company enjoys priority over the assets and moneys of the liquidated housing developer company, even at the expense of the aggrieved purchasers' interests.Owing to this, the rights of the purchasers are marginalised. Thus, following some analyses over the liquidation legal provisions and the housing law, this paper suggests certain proposals to improve the current state of law governing rehabilitation of failed residential projects in Malaysia to preserve the interests of the purchasers.